The Semitic languages : an international handbook - Weninger, Stefan (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2011)
The handbook The Semitic Languages offers a comprehensive reference tool for Semitic Linguistics in its broad sense. It is not restricted to comparative Grammar, although it covers also comparative aspects, including classification. By comprising a chapter on typology and sections with sociolinguistic focus and language contact, the conception of the book aims at a rather complete, unbiased description of the state of the art in Semitics. Articles on individual languages and dialects give basic facts as location, numbers of speakers, scripts, numbers of extant texts and their nature, attestation where appropriate, and salient features of the grammar and lexicon of the respective variety. The handbook is the most comprehensive treatment of the Semitic language family since many decades.